Influence of peers' actual appraisals on moral self-representations of Chinese adolescents - Yue, Caizhen; Long, Yihong; Ou, Kaihua; Dong, Xiaofang; Cao, Fasheng (Frontiers in Psychology, 2022)
Adolescence is a vital period of developing a moral self. As individuals enter adolescence, peers become increasingly important to them. This study aimed to explore the influence of actual appraisals of peers on moral self-representation.Based on Looking Glass Self Hypothesis, reflected appraisals usually have a mediating effect on others’ appraisals and self-appraisals. A total of 320 Chinese adolescents (aged 12-14) were surveyed by using the Chinese Moral Trait Words Rating Scale. Every two people were divided into a group of participants, and the members of the group filled in actual appraisals of peers, reflected appraisals, and self-appraisals questionnaires respectively.The results showed that: (a) Chinese adolescents had a certain accuracy in actual appraisals of peers, but often underestimated how their peers perceived them. (b) Actual appraisals of peers indirectly affected self-appraisals through reflected appraisals in the process of forming the adolescent moral self. This study was conducive to understanding the influence of peers on forming adolescent moral self under the background of Chinese culture.